CONFLICT OF INTEREST BETWEEN INDIVIDUAL AND STATE IN DAN BROWN'S DECEPTION POINT (2001): A SOCIOLOGICAL APPROACH - KHASANAH, SINTA NUR (2011)
The main aim of this study is to find how conflict of interest between individual and state is reflected in Dan Brown's Deception Point by correlating its structural elements and social historical background of United State of America in the late of 20th and early 21st century. Indeed, literature and sociology are bounded each other due to the assumption that the appearance of literary work is in social emptiness. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is Dan Brown's Deception Point meanwhile secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. The outcomes of this study are as follows: (1) Dan Brown's Deception Point reflects social condition occurred in United State of America in the late of 20th and early 21st century. (2) Dan Brown's Deception Point depicts conflict of interest between individual and state in united state of America. (3) Dan Brown's Deception Point is criticism toward unbalance situation and condition that can be found in character's characterization, narration and dialogue.